(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Laparoscopic cholecystectomy is the standard treatment for symptomatic gallstone disease, and creation of pneumoperitoneum is a critical step for providing adequate intra-abdominal visualization and instrument manoeuvrability. The open technique is widely used for controlled peritoneal entry. However, comparative data regarding the simplest and most effective site for first-port creation by the open technique remain limited. The present study compared different first-port sites during laparoscopic cholecystectomy. Objectives: To determine the simplest and most effective site for creation of the first port and pneumoperitoneum by the open technique during laparoscopic cholecystectomy, and to compare the approaches with respect to duration of port creation, surgeon position, complications, hospital stay and postoperative recovery. Methodology: This prospective comparative study was conducted among 100 patients undergoing laparoscopic cholecystectomy. The study compared open first-port placement using the infraumbilical and supraumbilical approaches, with assessment of the right- and left-sided approaches as described in the study protocol. Demographic characteristics, surgeon position, duration of first-port creation, duration of hospital stay, port-site infection, port-site hernia, bowel injury, biliary tree injury and days to resumption of normal activity were recorded. Statistical analysis was performed using chi-square testing, with p<0.05 considered statistically significant. Results: The mean age of the study population was 51.92±9.85 years, with 52% of patients belonging to the 51–60-year age group and 61% being female. There was no significant association between age and first-port site (p=0.673), and sex was similarly not significantly associated with port-site selection. A significant association was observed between the side of the surgeon and the first-port site (p<0.001). Duration of first-port creation was also significantly associated with port-site selection (p<0.001); 29 patients in the infraumbilical group achieved first-port creation within 2 minutes compared with none in the supraumbilical group. Duration of hospital stay was significantly associated with port-site selection (χ²=11.408, p=0.001), with longer hospital stay observed in the supraumbilical group. No significant association was found between first-port site and port-site infection (p=0.081), port-site hernia (p=0.400), or time to resumption of normal activity (p>0.05). No bowel or biliary tree injury was documented. Conclusion: The right-sided infraumbilical approach was the simplest and most efficient approach for routine creation of the first port by the open technique in the present study. It was associated with shorter access time and fewer technical difficulties, while postoperative complications and functional recovery were broadly comparable between the approaches. Left-sided infra-/supraumbilical access may be reserved for selected patients in whom conventional midline access is less suitable, particularly those with previous abdominal procedures or altered anatomy.